Construction of dna vaccine expressing serine repeat antigen (sera) malarial epitope of plasmodium falciparijm - Nadia, Sedi (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Malaria remains a serious public health problem and caused an estimated 2 million people death worldwide annually. The current eontrol and treatment strategies are not effective in eradicating malaria. 1n addition, the rising rates ot malaria drug resistant parasite in some area worsen the situation especially against P. falciparum. Therefore, a more effective vaeeine against malaria parasite is urgently needed. DNA vaeeination is a new approaeh to control the malaria. Previous animai studies have shown that DNA vaccination was abie to induce both humoral and cellular responses. In order to resolve this problem an asexual blood stage antigen of P. falciparum, serine repeat antigen (SERA) is reported to be one of the promising vaccine candidates. In this study A DNA vaccine expressing a synthetic 22 kDa protein (SE22) from the 47 kDa N-terminal domain of SERA was eonstrueted. The p V AXi- SE22 construct was verified by PCR screening and sequencing. Hopefully thls DNA vaccine will be further studied to reveal its potential in reducing malarial morbidity and mortality.